Platelet VPS16B is dependent on VPS33B expression, as determined in two siblings with arthrogryposis, renal dysfunction, and cholestasis syndrome. (12th April 2022) - Penon‐Portmann, Monica; Westbury, Sarah K.; Li, Ling; Pluthero, Fred G.; Liu, Richard J. Y.; Yao, Helen H. Y.; Geng, Ryan S. Q.; Warner, Neil; Muise, Aleixo M.; Lotz‐Esquivel, Stephanie; Howell‐Ramirez, Marianela; Saborío‐Chacon, Pablo; et al.
Abstract: Background: Platelet α‐granule biogenesis in precursor megakaryocytes is critically dependent on VPS33B and VPS16B, as demonstrated by the platelet α‐granule deficiency seen in the rare multisystem disorder arthrogryposis, renal dysfunction, and cholestasis (ARC) syndrome associated with biallelic pathogenic variants in VPS33B and VIPAS39 (encoding VPS16B). VPS33B and VPS16B are ubiquitously expressed proteins that are known to interact and play key roles in protein sorting and trafficking between subcellular locations. However, there remain significant gaps in our knowledge of the nature of these interactions in primary cells from patients with ARC syndrome. Objectives: To use primary cells from patients with ARC syndrome to better understand the interactions and roles of VPS33B and VPS16B in platelets and precursor megakaryocytes. Patients/methods: The proband and his male sibling were clinically suspected to have ARC syndrome. Confirmatory genetic testing and platelet phenotyping, including electron microscopy and protein expression analysis, was performed with consent in a research setting. Results: We describe the first case of ARC syndrome identified in Costa Rica, associated with a novel homozygous nonsense VPS33B variant that is linked with loss of expression of both VPS33B and VPS16B in platelets. Conclusion: These results indicate that stable expression of VPS16B in platelets, their precursor megakaryocytes, and other cells is dependent on VPS33B. We suggest that systematic evaluation of primary cells from patients with a range of VPS33B and VIPAS39 variants would help to elucidate the interactions and functions of these proteins.